Activation of human basophils by combined toll‐like receptor‐ and FcεRI‐triggering can promote Th2 skewing of naive T helper cells. Issue 2 (13th November 2013) - Suurmond, Jolien; Stoop, Jeroen N.; Rivellese, Felice; Bakker, Aleida M.; Huizinga, Tom W. J.; Toes, René E. M.
<x xml:space="preserve">Abstract</x> Basophils are mostly known for their involvement in allergic reactions. Recent studies in mice indicate a role for basophils in the induction of adaptive immunity, especially T helper 2 (Th2) responses. Therefore, it would be highly important to understand how basophils respond to pathogen‐associated molecules, such as ligands for toll‐like receptors (TLRs), and if the basophils could promote Th2 responses via these stimuli. To this end, the activation of basophils via TLRs in combination with activation via IgE was studied, as well as its effect on T helper cell skewing. Using quantitative PCR, we demonstrated the presence of mRNA for TLRs 1–8 in human basophils. Basophils responded to TLR triggering with differential cytokine production, but not with degranulation. Simultaneous triggering of TLRs and IgE led to synergy in production of IL‐4, IL‐8, IL‐13, and RANTES. Furthermore, the synergistic effects on basophils mediated by IgE and TLR‐4 triggering allowed robust Th2 skewing upon activation of naïve human CD4+ T cells. Our data show that human basophils respond to TLR ligands in synergy with IgE‐mediated activation and that the cytokines produced can promote Th2 differentiation. These results indicate a role for basophils in the regulation of T‐cell responses in humans.